Assessing spleen stiffness by point shear‐wave elastography: Is it feasible and reproducible in patients with chronic liver disease? Is it useful to predict portal hypertension?. Issue 5 (10th October 2019) - Fraquelli, Mirella; Conti, Clara Benedetta; Giunta, Mariangela; Gridavilla, Daniele; Tosetti, Giulia; Baccarin, Alessandra; Casazza, Giovanni; D'Ambrosio, Roberta; Nicolini, Antonio; Primignani, Massimo; Vecchi, Maurizio; Lampertico, Pietro; et al.
Summary: Background and aims: To assess the feasibility and reproducibility of the spleen stiffness (SS) measurement by point shear‐wave elastography (pSWE) in a cohort of compensated chronic liver disease (CLD) patients [Cohort 1] and to investigate pSWE accuracy to predict clinically relevant portal hypertension (PH) in a consecutive cohort of cirrhotics with endoscopic signs of portal hypertension [Cohort 2] . Methods: [Cohort 1]: 186 consecutive CLD patients underwent abdominal ultrasound (US), liver stiffness (LS) and SS measurement by pSWE and transient elastography (TE) and liver biopsy. Inter‐rater agreement of SS (pSWE) was evaluated by intra‐class correlation coefficient (ICC). [Cohort 2]: 80 cirrhotics underwent US, LS and SS (by pSWE and TE), hepatic venous pressure gradient (HVPG) measurement and upper endoscopy. Linear correlations between LS or SS and HVPG and linear regression analysis were performed to establish determinants of HVPG > 16. Results: [Cohort 1] SS measurement failure was 3.4% for pSWE and 13.8% for TE. For pSWE the ICC between two independent examiners was 0.74 (95% CI, 0.66‐0.80). [Cohort 2]: SS measurement failure was 2.5% for pSWE and 48% for TE. HVPG and LS did not correlate. Significant correlation was observed between HVPG and SS (r = 0.36, P  = .001). At multivariate analysis only the presence of ascites and SS values significantly correlated with HVPG > 16, a threshold of high mortality risk cirrhosis. Conclusions: Measuring SS by pSWE is feasible and reproducible in CLD and is applicable in most cirrhosis cases as a promising tool of prognosis and a surrogate marker of the HVPG threshold related to survival‐ and liver‐related outcomes.